Mengevaluasi Transformasi Disiplin Spiritual menjadi Disiplin Belajar melalui Studi Kuantitatif tentang Ibadah Harian untuk Meningkatkan Regulasi Diri Akademik - Muhammad Cholid Abdurrohman; Raushan Fikri Adam; Septyayu Catur Pamungkas (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
Daily religious practice theoretically fosters executive functions and cognitive control, yet empirical evidence regarding its impact on learning management remains limited. This study aims to investigate the influence of daily religious habits on students' academic self-regulation. Employing a quantitative method, the study involved a sample of 187 secondary school students. Data were collected using a validated Likert-scale self-report questionnaire. The primary analysis utilized a simple linear regression test, subsequently validated through a robustness check using Spearman's Rho non-parametric correlation. Empirical results reveal a positive and significant relationship between daily religious habits and academic self-regulation (ρ< .01). The resulting regression equation is Y=3.911+ 0.750X, with a coefficient of determination (R2) of .356. These findings confirm that the intensity of religious practice contributes 35.6% to students' learning autonomy. The robustness check consistently validated the model (rs=0.541). Spiritual practices appear to activate mechanisms, such as delayed gratification and religious coping, that mitigate academic procrastination. In conclusion, this study provides an empirical foundation for educational transformation; religious routines in schools should no longer be viewed merely as moral tools but as a rational infrastructure that translates spiritual discipline into academic discipline. Educational institutions are encouraged to redesign classroom instruction by strategically integrating religious habits to cultivate autonomous learners with robust self-regulation capabilities.